Analysis of the Case PT Metro Mini Sues the Limited Liability Company Law to the Constitutional Court - Aimmatul Khoiroh; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The General Meeting of Shareholders (GMS) is the highest institution and part of the Company as a place for shareholders to make important decisions whose authority is not given to the Board of Directors or the Board of Commissioners within the limits determined by law and/or the Articles of Association. The law is based on Article 1 paragraph 4 of the Limited Liability Company Law. Pursuant to Article 86 paragraph 1 of the Limited Liability Company Law, a GMS can be held if more than 1/2 of the total shares with voting rights are present or represented, unless the law and/or articles of association determine a larger quorum. In the second GMS as referred to in paragraph 2 is valid and a decision can be made if in the GMS at least 1/3 of the total shares are represented or represented, unless the articles of association determine a larger quorum based on the provisions of Article 86 paragraph 4 of the Limited Liability Company Law. If the quorum for the second GMS as referred to in Article 86 paragraph 4 is not reached, the Company may request the chairman of the district court whose jurisdiction covers the Company's position to determine a quorum for the third GMS based on the provisions of Article 86 paragraph 5. The GMS will have a grace period regarding the implementation of the second GMS and third, namely no later than 10 (ten) days and no later than 21 (twenty one) days after the GMS that preceded it was held, according to the provisions of Article 86 paragraph 9 of the Limited Liability Company Law it becomes a matter to be decided by the Constitutional Court. The problem caused by the Judicial Review of Article 86 paragraph 9 of Law Number 40 of 2007 concerning Limited Liability Companies is due to the length of time in which the decision of the District Court was received in the implementation of the GMS made the results of the implementation of the Third GMS of PT. Metro Mini was blocked in the Ministry of Law and Human Rights system so that it became a loss in the legality of the Metro Mini company due to the holding of the Third GMS of PT. Metro Mini is carried out more than the time specified in Article 86 paragraph 9 of the Limited Liability Company Law. Therefore, the Government should immediately revise Law Number 40 of 2007 concerning Limited Liability Companies, in particular Article 86 paragraph 9 which previously stated "The second and third GMS shall be held within a period of no sooner than 10 (ten) days and no later than 21 (twenty one) ) days after the GMS that precedes it is held” becomes “the second and third GMS is held within a period of no sooner than 10 (ten) days and no later than 21 (twenty one) days after the GMS that precedes it is held or in the event that the GMS is held based on a court order This is no later than 21 (twenty one) days after the district court's decision is obtained. Because of the Constitutional Court Decision No. 84/PUU-XI/2013, so that the meaning of the Constitutional Court's decision becomes a positive norm reference, because the Indonesian legal system adheres to the continental European legal system.